Parkin regulation of CHOP modulates susceptibility to cardiac endoplasmic reticulum stress - Han, Kim; Hassanzadeh, Shahin; Singh, Komudi; Menazza, Sara; Nguyen, Tiffany T.; Stevens, Mark V.; Nguyen, An; San, Hong; Anderson, Stasia A.; Lin, Yongshun; Zou, Jizhong; Murphy, Elizabeth; et al. (Scientific reports, 2017)
The regulatory control of cardiac endoplasmic reticulum (ER) stress is incompletely characterized. As ER stress signaling upregulates the E3-ubiquitin ligase Parkin, we investigated the role of Parkin in cardiac ER stress. Parkin knockout mice exposed to aortic constriction-induced cardiac pressure-overload or in response to systemic tunicamycin (TM) developed adverse ventricular remodeling with excessive levels of the ER regulatory C/EBP homologous protein CHOP. CHOP was identified as a Parkin substrate and its turnover was Parkin-dose and proteasome-dependent. Parkin depletion in cardiac HL-1 cells increased CHOP levels and enhanced susceptibility to TM-induced cell death. Parkin reconstitution rescued this phenotype and the contribution of excess CHOP to this ER stress injury was confirmed by reduction in TM-induced cell death when CHOP was depleted in Parkin knockdown cardiomyocytes. Isogenic Parkin mutant iPSC-derived cardiomyocytes showed exaggerated ER stress induced CHOP and apoptotic signatures and myocardium from subjects with dilated cardiomyopathy showed excessive Parkin and CHOP induction. This study identifies that Parkin functions to blunt excessive CHOP to prevent maladaptive ER stress-induced cell death and adverse cardiac ventricular remodeling. Additionally, Parkin is identified as a novel post-translational regulatory moderator of CHOP stability and uncovers an additional stress-modifying function of this E3-ubiquitin ligase.